Interventional Radiology Procedures for Chronic Pain and Palliative Care: A Systematic Review Focused on Ablation and Neurolysis (2015–2025) - Belladina Mayyasha Martadipura; Raudina Fisabila Martadipura (TIN: Terapan Informatika Nusantara, 2026)
Chronic and cancer-related pain impose substantial global health burdens and contribute to long-term opioid dependence. Image-guided percutaneous ablation and chemical neurolysis have emerged as important alternative option when pharmacologic therapy is insufficient or poorly tolerated, yet evidence remains heterogeneous across indications and techniques. Therefore, this systematic review aims to evaluate the efficacy, safety, and opioid-sparing effects of image-guided ablation and chemical neurolysis in oncologic and non-oncologic pain populations (2015–2025). Following PRISMA 2020 guidelines, a comprehensive search of major biomedical databases identified studies involving adult patients undergoing image-guided thermal ablation or chemical neurolysis. Major biomedical databases, including PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Science Direct and EuropePMC were searched. Eligible studies included adult populations undergoing image-guided ablation or neurolysis or neuromodulation. Risk of bias was assessed using RoB 2, ROBINS-I, and Joanna Briggs Institute tools. A narrative synthesis was performed. Forty-five studies (24 randomized controlled trials and 21 observational cohorts or case series) were included. Ablative techniques demonstrated clinically meaningful and, in selected indications, durable pain reduction across musculoskeletal and oncologic conditions. Chemical neurolysis showed significant benefit in visceral cancer pain and emerging applicability in selected non-oncologic settings. Across modalities, major procedure-related complications were uncommon, and no consistent procedure-related mortality was reported. Several studies documented reductions in opioid requirements following intervention. Conclusion: Image-guided ablation and neurolytic procedures provide effective pain relief with generally favorable safety profiles across diverse clinical contexts. These interventions may support opioid-sparing strategies and warrant structured integration into multidisciplinary pain management pathways.